Inovasi Dan Desain Turbin Hidrokinetik Darrieus Berdasarkan Bentuk Distribusi Kecepatan Aliran - Citra Sari Wardani; Dwi Anung Nindito; Allan Restu Jaya (Media Ilmiah Teknik Sipil, 2020)
Darrieus turbine use blades with a hydrofoil shape, so the rotational ability is influenced by lift force. This caused the initial rotation capability to be very low when compared to the drag turbine type. The flow velocity distribution in the vertical direction indicates a small cross-sectional speed of flow approaching the base of the flow channel, then rising towards the surface. Darrieus Spinning Top turbine is the result of innovation and design based on the concept of flow velocity distribution. Darrieus Spinning Top turbine’s blade shapes are circular-arc and straight-line, adjusting flow velocity distribution of 0.2H, 0.6H and 0.8H from the top of the turbine. In this study, a performance comparison was conducted between Darrieus turbine and Spinning Top Darrieus. Darrieus turbines produce RPM and torque values of 54.59 – 67.90 and 0.014 – 0.029 Nm, respectively. Darrieus Spinning Top turbines produce RPM values and torque of 69.24 – 82.02 and 0.012 – 0.020 Nm respectively. RPM improvements in Darrieus Spinning Top turbine design increase the influence of lift force (increased λ value). This results in a high lap rate, but requires a high self starting to perform the turbine rotation cycle.